PEMBAGIAN WARIS PADA KELUARGA ISLAM (STUDI KASUS DI DUSUN WONOKOYO KELURAHAN MENGANTI KECAMATAN MENGANTI KABUPATEN GRESIK) - mizatul khaula; Ahmad Subekti; Dzulfikar Rodafi (Fakultas Agama Islam UNISMA, 2020)
Provisions for the distribution of inheritance for people left by the testator have been outlined in the Qur'an and the Hadith of the Prophet in detail and clearly. The verses of the Qur'an and the Hadith of the Prophet directly regulate inheritance and without ignoring someone at all. From the background of the research above, the researcher formulated the problem, namely regarding the view of Islamic law on the distribution of inheritance systems in Muslim families and the practice of inheritance among Muslim families. The method of study in this paper uses qualitative methods. Data collection procedure is done using the observation method, interview method, and documentation methods. In this study shows that the view of Islamic law on the distribution system of inheritance in Muslim families still more or less using customary inheritance law, but prioritizing using Islamic inheritance law first. And in the distribution system uses what is already listed in the Qur'an and al-Hadith. In practice, if there is a family member who has not agreed on the distribution, then it is shared evenly or by family agreement. the conclusion is that the distribution system of inheritance is in accordance with Islamic law, because there is no quarrel between heirs. in practice, there are still a few that use customary law or are equally between men and women.Keywords: Inequality, Inheritance, Islamic LawProvisions for the distribution of inheritance for people left by the testator have been outlined in the Qur'an and the Hadith of the Prophet in detail and clearly. The verses of the Qur'an and the Hadith of the Prophet directly regulate inheritance and without ignoring someone at all. From the background of the research above, the researcher formulated the problem, namely regarding the view of Islamic law on the distribution of inheritance systems in Muslim families and the practice of inheritance among Muslim families. The method of study in this paper uses qualitative methods. Data collection procedure is done using the observation method, interview method, and documentation methods. In this study shows that the view of Islamic law on the distribution system of inheritance in Muslim families still more or less using customary inheritance law, but prioritizing using Islamic inheritance law first. And in the distribution system uses what is already listed in the Qur'an and al-Hadith. In practice, if there is a family member who has not agreed on the distribution, then it is shared evenly or by family agreement. the conclusion is that the distribution system of inheritance is in accordance with Islamic law, because there is no quarrel between heirs. in practice, there are still a few that use customary law or are equally between men and women.Â Keywords: Inequality, Inheritance, Islamic Law